Political Science in the Shadow of the State
XXI, 344 p. 9 illus., 6 illus. in color.
Keywords: ‘This compelling volume literally spans the globe, from North America to Europe and on to the Middle East, as it apprehends how agenda-setting and research support by public authorities can redirect and limit the contours and content of political science. Sharply argued, the essays raise many points of concern’. —Ira I. Katznelson, Ruggles Professor of Political Science and History, Columbia University, USA ‘Superbly evocative…A distinguished dissection of a prevalent pattern in contemporary state-scholar relationships, revealed as disquieting in terms of its costs to intellectual freedom and social capital. Also a compassionate appeal in favor of expanding political scientists’ topic-driven international cooperation’. —Irmina Matonyte, former President, Lithuanian Political Science Association, Military Academy of Lithuania (Vilnius) ‘Political science should be relevant, but this book makes a convincingargument that the state should not be left to define what is relevant. A discipline focused on power and how to control it would do well to reflect and act on the warnings embodied in this work’. —Gerry Stoker, Professor of Governance, University of Southampton, UK What is the link between scholarship and democracy? What role do academics play in sustaining democratic values? Why should concerns about the ‘hollowing-out’ of democracy include a focus on the changing governance of higher education? Offering the first comparative analysis of how both democratic and autocratic politicians are seeking to control the research funding landscape, this book reveals a very worrying shift in the relationships between the state and universities: With higher education politically redefined as a mere tool of economic strategy, the space for academic autonomy, intellectual independence and critical thinking is being closed down. This book will be of interest to anyone concerned about democratic governance and the future of higher education. Rainer Eisfeld is Professor Emeritus of Political Science at Osnabrück University, Germany, and also taught at UCLA as a Visiting Professor. Matthew Flinders is Founding Director of the Sir Bernard Crick Centre and Professor of Politics at the University of Sheffield, UK.